1997
DOI: 10.1111/j.1445-5994.1997.tb00985.x
|View full text |Cite
|
Sign up to set email alerts
|

Interferon therapy for acute hepatitis C viral infection ‐ a review by meta‐analysis

Abstract: Short term (six weeks to six months) treatment of symptomatic acute HCV with interferon (both alpha and beta) produced a better long term response rate than prolonged therapy (> 12 months) in chronic HCV. Daily doses of 6MU and 10MU produced better responses than 3MU but more studies are needed to determine the optimum regime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…60 It has been suggested that early treatment of acute hepatitis increases the likelihood of clearing the infection. 66 ' 67 Although treatment is aimed at clearing HCV carriage and preventing the development of cirrhosis, patients with cirrhosis can also improve with therapy by both viral clearance and improvements in liver histology. 68 Currently a wide range of options for treating HCV infection are under investigation.…”
Section: Treatment Of Hcv Infectionmentioning
confidence: 99%
“…60 It has been suggested that early treatment of acute hepatitis increases the likelihood of clearing the infection. 66 ' 67 Although treatment is aimed at clearing HCV carriage and preventing the development of cirrhosis, patients with cirrhosis can also improve with therapy by both viral clearance and improvements in liver histology. 68 Currently a wide range of options for treating HCV infection are under investigation.…”
Section: Treatment Of Hcv Infectionmentioning
confidence: 99%
“…Approximately 70% of infected persons develop chronic hepatitis, and between 20%–30% of infected persons may develop cirrhosis 2, 3. Several controlled and uncontrolled trials4–10 using different doses and durations of conventional interferon α (IFN‐α) monotherapy in acute HCV reported viral clearance rates ranging between 37% and 100% in IFN‐α–treated patients compared with only 12%–20% of untreated subjects. Most of these studies were problematic because of the small number of subjects, the diverse enrollment criteria, the different types and doses of IFN‐α, the differences in the definition of response, and the duration of follow‐up 11.…”
mentioning
confidence: 99%
“…Results for combined interferon and ribavirin in acute treatment of hepatitis C infection are currently inconclusive. The optimal timing of acute therapy after exposure remains uncertain, but some studies report similar results for immediate therapy and therapy that is delayed by 3–6 months 7 , 14 , 23 . ‐ 25 …”
Section: Implications Of Infection In Healthcare Workersmentioning
confidence: 99%